Consciousness modulates the automatic change detection of masked emotional faces: Evidence from visual mismatch negativity. (July 2020) - Chen, Bin; Sun, Pei; Fu, Shimin
Abstract: The ability to automatically detect changes in the environment is crucial for organisms to survive. In the visual system, changes in visual stimuli may evoke visual mismatch negativity (vMMN), an event-related potential (ERP) component that reflects automatic change detection. Previous studies that used visual masking to examine the effects of consciousness did not yield evidence that vMMN could be elicited by subliminal stimuli. However, these studies used relatively simple visual features. To further examine the role of consciousness in vMMN, the present study used emotional (happy and fearful) faces, which are biologically and socially significant visual stimuli. A passive oddball paradigm was employed, and we found that only fearful faces could evoke vMMN at a low consciousness level. Furthermore, the fear-related vMMN was enhanced by the consciousness level, and localized in regions of the brain associated with emotional face processing and the prefrontal cortex. We also found that the emotional visual mismatch oscillatory responses (vMORs) were associated with the enhancement of the alpha-band oscillation. Moreover, consciousness could weaken the happiness-related vMOR. These results suggested that changes to emotional faces—especially fearful faces—could be unconsciously detected by the brain. More importantly, this automatic change detection mechanism could be modulated by consciousness. Highlights: Fearful faces elicit visual mismatch negativity in the subliminal condition. The brain can detect changes of emotional faces in the subliminal condition. The automatic change detection of emotional faces is enhanced by consciousness. This effect is localized in the prefrontal cortex and emotional processing areas. The alpha-band EEG oscillations are associated with the visual mismatch responses.